2012
DOI: 10.1177/0149206311433855
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Passion

Abstract: This study examines the role of passion among entrepreneurs. In particular, the authors integrate identity theory with the literature surrounding passion to investigate the possible pathways through which entrepreneurial identities might influence passion, as well as the relationship between entrepreneurs’ passion and behavior. Structural equation modeling of responses from 221 entrepreneurs suggests that passion rises and falls in connection with entrepreneurial identity centrality and, furthermore, that pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
187
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(203 citation statements)
references
References 92 publications
(188 reference statements)
13
187
0
3
Order By: Relevance
“…Given that previous research has suggested that many people identify themselves with the object of their passion (Murnieks, Mosakowski, & Cardon, 2014;Vallerand & Houlfort, 2003), one could argue that participants in this study are passionate about their job, which seems to have become part of their identity. This finding adds to empirical evidence from recent studies (e.g., Oja et al, 2015;Swanson & Kent, 2015) that employees' identification in the sport industry is not restricted to the team, but extends to the organisation itself.…”
Section: Discussionmentioning
confidence: 82%
“…Given that previous research has suggested that many people identify themselves with the object of their passion (Murnieks, Mosakowski, & Cardon, 2014;Vallerand & Houlfort, 2003), one could argue that participants in this study are passionate about their job, which seems to have become part of their identity. This finding adds to empirical evidence from recent studies (e.g., Oja et al, 2015;Swanson & Kent, 2015) that employees' identification in the sport industry is not restricted to the team, but extends to the organisation itself.…”
Section: Discussionmentioning
confidence: 82%
“…There is empirical evidence for a positive effect of passion in the postlaunch phase of the entrepreneurial process as well (Baum & Locke 2004, Murnieks et al 2012. However, it is also important to note that entrepreneurial passion may be an outcome of entrepreneurs' actions.…”
Section: Motivational/affective Factorsmentioning
confidence: 99%
“…Different personality traits are a fact of life (Keogh 1992). Therefore, it is normal that academics have different opinions and needs with respect to motivational mechanisms (Murnieks et al 2014;Song and Chathoth 2013). Occasionally, academics exhibit different attitudes and behaviours when college managers use the same communication approach to improve the motivational mechanism.…”
Section: Methods Research Hypothesesmentioning
confidence: 99%